Effect of high pressure torsion process on the microhardness, microstructure and tribological property of Ti6Al4V alloy. (20th December 2021) - Deng, Guanyu; Zhao, Xing; Su, Lihong; Wei, Peitang; Zhang, Liang; Zhan, Lihua; Chong, Yan; Zhu, Hongtao; Tsuji, Nobuhiro
Highlights: Bulk nanostructured Ti6Al4V alloy with average grain size of about 50 nm was obtained by HPT process at 7.5 GPa. Microhardness was greatly increased and saturated to about 430 hv after 10 HPT revolutions. For the first time, influence of HPT process on the tribological properties of Ti6Al4V alloy was conducted. Ti6Al4V alloy had good potential into structural applications due to its remarkably improved mechanical and tribological properties. Abstract: In the present study, a fully lamellar Ti6Al4V alloy was severely deformed by high pressure torsion (HPT) process under a pressure of 7.5 GPa up to 10 revolutions. Experimental results revealed that the microhardness of Ti6Al4V was increased remarkably by about ∼ 41% and saturated at about 432 Hv after the HPT process. A relatively uniform bulk nanostructured Ti6Al4V alloy with an average grain size of about 52.7 nm was obtained eventually, and no obvious formation of metastable ω phase was detected by XRD analysis. For the first time, the tribological properties of the HPT processed Ti6Al4V alloy were investigated by a ball-on-disc test at room temperature under a dry condition. It was found that HPT process had a great influence on the friction and wear behaviors of Ti6Al4V alloy. With increasing the number of HPT revolutions, both friction coefficient and specific wear rate were obviously decreased due to the reduction of abrasion and adhesion wears. After being deformed by 10 HPT revolutions, the friction coefficient was reduced from about 0.49 to 0.37, and the specific wear rate was reduced by about 48%. The observations in this study indicated that HPT processed Ti6Al4V alloys had good potential in structural applications owing to their greatly improved mechanical and tribological properties. Graphical abstract: Image, graphical abstract